Green Marketing: Initiatives in the Indian Context - Yadav, Rambalak; Pathak, Govind Swaroop (Indian Journal of Marketing, 2013)
Protection of the environment is an issue of key concern which has permeated into all spheres of life. Consumers are increasingly becoming concerned about the environment and various issues related to it at the global level. This change has encouraged a couple of organizations and has also compelled many organizations to respond with 'environmentally' friendly products. Green marketing is perceived as an opportunity by many organizations to achieve their long term goals. Green marketing incorporates a broad range of activities, including product modifications, changes to the production processes, packaging changes, as well as modifying advertising. This paper attempts to examine the concept of green marketing, the various challenges and opportunities associated with it, as well as study the various initiatives taken in the Indian context by various organizations as well as by the Government. The discussion reveals that green marketing is gaining importance in India for various issues concerning sustainable development.